Application of Ionizing Radiation for the Enhancement of Hydrogen Yield in Electrolytic Water Decomposition - Ulmer, W. (European Journal of Applied Sciences, 2022)
During the past decay many experimental configurations to improve the yield of hydrogen by electrolysis. These attempts include tests of different materials for the electrodes. This study proposes the use of γ-radiation of waste sources of nuclear reactors. The related experimental configuration can be reduced to boxes filled with water exposed to ionizing radiation and capacitors as electrodes as well-known in other technical disciplines. Test measurements based on radiation of a linear accelerator (6 MV beam) provided significant differences of the yield of hydrogen between with and without radiation.